Development of Key Performance Indicators of Municipality by Applying an Analytical Hierarchy Process: Case Study of Lower Northeastern Thailand, Group II - PORNPRASERT, Peema; POONIKOM, Kanisorn (Walailak Journal of Science and Technology (WJST), 2015)
The purpose of this research was to develop key performance indicators (KPIs) in municipalities by applying a priority assessment in particular areas of lower Northeastern Thailand, Group II. Questionnaires were used to gather data from 200 municipality office administrations and 17 experienced professionals. To begin with the investigation of KPIs concerned the competency of municipality. The criteria of competency were categorized initially into 5 parts. All KPIs were analyzed by the Nominal Group Technique (NGT) and Affinity Diagram Technique (ADT). Grouped KPIs were then used to construct a questionnaire to provide both validity and reliability. For data analysis, confirmatory factor analysis using Bartlett’s Test Sphericity technique was used. Professionals later evaluated the priority assessment with an Analytical Hierarchy Process (AHP). It found that all the 487 KPIs formerly used can be extracted into 38 KPIs. To beneficial contribution, it is cost saving and consistency to assess the competency in municipality office in Thailand.